0016 Birthing hospitals' policies and practices related to infant safe sleep: a statewide survey in massachusetts. (26th April 2015) - Hackman, Holly; McGuire, Colleen; KautzMills, Julie; Barber, Cathy; Pavlos, Carlene; Egan, Justine; Muzhuthett, Paul
Abstract : Statement of purpose: Sudden unexpected infant death (SUID) is the leading cause of post-neonatal infant death in Massachusetts. Multidisciplinary reviews have found that many are associated with unsafe infant sleep positions and environments. The hospital nursery is a place where infant care is modelled and parents receive education. Knowing the prevalence of hospital policies, practices and trainings related to safe sleep is valuable for informing SUID prevention. Methods/Approach: An on-line survey of maternity department managers was sent to all 49 birthing hospitals/centres in Massachusetts. Questions included staff training on infant safe sleep, infant side sleeping practices, presence of a written policy, parent education, perceived barriers to promoting safe sleep and needed areas of support. The survey was administered from April through September 2013 with 100% response rate. Results: Forty-six percent of birthing hospitals had a written infant "safe sleep" policy. Of these, "back only" sleep was the most common component (95%), followed by exclusion of soft crib items (82%), and avoidance of general co-bedding (82%), co-bedding multiples (68%), encouraging co-rooming (68%), and avoidance of overheating (77%). Twenty-six percent had a written policy with all six components. Nearly all (94%) trained staff. Only 27% reported side sleeping of "spitty" infants was "never done". Nearly all indicated safe sleep was part of educational materials. Leading barriers to promoting safe sleep were family beliefs (81%) and language (33%). Conclusions: Birthing hospitals and centres in Massachusetts have different policies and practices on infant safe sleep and most do not incorporate several select prevention measures recommended in the 2011 AAP guidelines. Most of the respondents felt that a model policy, provided by the state, would be useful. Significance and contribution to the field: This is a universal survey of reported policies and practices related to infant safe sleep in birthing hospitals/centres in Massachusetts. The findings provide valuable information for prevention efforts in other states.